2013
DOI: 10.1590/s1983-14472013000200003
|View full text |Cite
|
Sign up to set email alerts
|

Associação das sub-escalas de Braden com o risco do desenvolvimento de úlcera por pressão

Abstract: Pressure ulcers (PU) may increase the incidence of hospital complications, and one should prevent this damage. The Braden Scale stands out as a tool to assess the risk of PU. The study aimed to identify changes in the score of the Braden subscales are associated with the risk of developing PCU. Logistic regression was used in a retrospective cohort study conducted in Hospital de Clínicas de Porto Alegre in adults hospitalized in surgical clinical units from October 2005 to June 2006. We evaluated the records d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 14 publications
2
14
0
11
Order By: Relevance
“…Likewise, a Portuguese study proposed two simplified scales to evaluate their predictive ability against the Braden scale, and the original scale was elucidated to have the best predictive capacity. 43 The above findings may conclude that the clinical effectiveness of the scale transcends across countries and settings. 27 In summary, while the Braden scale is ultimately not perfect in risk prediction, it should not be further simplified as it possesses the best predictive capability with six conceptualised risk factors (subscales).…”
Section: Predictors Of Pi Developmentmentioning
confidence: 80%
See 1 more Smart Citation
“…Likewise, a Portuguese study proposed two simplified scales to evaluate their predictive ability against the Braden scale, and the original scale was elucidated to have the best predictive capacity. 43 The above findings may conclude that the clinical effectiveness of the scale transcends across countries and settings. 27 In summary, while the Braden scale is ultimately not perfect in risk prediction, it should not be further simplified as it possesses the best predictive capability with six conceptualised risk factors (subscales).…”
Section: Predictors Of Pi Developmentmentioning
confidence: 80%
“…The Braden scale appeared to be the most predictive form of PI risk assessment compared with all of the subscales. Likewise, a Portuguese study proposed two simplified scales to evaluate their predictive ability against the Braden scale, and the original scale was elucidated to have the best predictive capacity . The above findings may conclude that the clinical effectiveness of the scale transcends across countries and settings …”
Section: Discussionmentioning
confidence: 90%
“…By studying adult patients admitted at the Clinical Hospital of Porto Alegre, Rio Grande do Sul State, Brazil, the researchers found that any reduction in activity level increased by eight times the risk of developing PU (Zambonato et al, 2013). In another study in an LTI, the sub-scale activity was the second largest predictor of PU, second only to friction and shear (Lahmann, Tannen, Dassen, & Kottner, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…The results of this study demonstrate that the Braden Scale is a resource that should be employed in the elderly daily care in LTI for both the prevention of PU and for its proper management. The scale of usefulness is not limited to its total score; in contrast, it is increased with the analysis of its subscales that has the ability to define the risk factor for the development of PU (Zambonato, Assis, & Beghetto, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Houve predomínio do sexo feminino 67(58,8%) em relação ao número de participantes e quanto ao desenvolvimento de LPP dos sete casos 3 (2,7%) eram mulheres. No que diz respeito à associação entre a variável sexo e desenvolvimento de LPP há divergência nos estudos brasileiros, de tal forma que não apresenta precisão quanto ao desfecho (15)(16) .…”
Section: Discussionunclassified